Psychological Features of Acquisition of Foreign Language for Specific Purposes (The Journal of Psychology and Sociology, 2019)
The purpose of this article is to reveal the psychological and pedagogical features of joint-dialogical cognitive activity (SDPD) in teaching a foreign language, which is formed into a single psychological structure during the interaction and communication of the teacher and students. The problem of poor digestibility of a foreign language despite the high motivation due to the increased demand for a foreign language in modern life depends entirely on a systematic approach to learning from a psychological point of view. In this aspect of student training, the teaching of foreign languages is important. Improving the field of education and orienting it to enter the world educational space pose to higher education the serious tasks of forming highly qualified specialists able to think creatively and be competitive in the labor market. The quality of training future specialists involves not only improving the quality of students’ knowledge in all studied disciplines, but also developing a multicultural personality with universal values, respecting the language, traditions, and culture of various nations. Key words: action motif,psychological, an activity idea.